Climate‐Driven Range Shifts and Conservation Challenges for Brown Bears in Türkiye - Ercan Sıkdokur; İsmail K. Sağlam; Çağan H. Şekercioğlu; Irfan Kandemir; Ali Onur Sayar; Morteza Naderi (Ecology and Evolution)
ABSTRACT Understanding the current and future distribution of wildlife species is crucial for effective conservation planning, particularly in the face of climate change and increasing anthropogenic pressures. This study aims to assess the potential distribution of brown bears across Türkiye both presently, by 2050 and 2070, considering various climate change scenarios, evaluating habitat vulnerability, and reassessing the effectiveness of protected areas. Using an ensemble forecasting approach, we modeled brown bears' current and future habitat suitability, incorporating 608 occurrence records along with bioclimatic, topographic, and anthropogenic predictors under climate scenarios. Our model estimates that approximately 17.3% of Türkiye (135,556 km2) currently offers suitable habitat for brown bears with the highest suitability found in the Euro‐Siberian (46%), Irano‐Turanian (43%), and Mediterranean (11%) biogeographic regions. The results indicate that climate change combined with anthropogenic pressures, is expected to reduce brown bear habitat suitability by 40%–48% by 2050, and 40%–67% by 2070 under various scenarios. A significant contraction in the brown bears' range, along with a northward shift in suitable habitats, is projected, reflecting the broader impacts of climate. Additionally, the suitability of brown bear habitats is estimated to be strongly influenced by the changes in altitude. The proportion of suitable habitats under protection is projected to decline from 21.4% to 15%–16.1% by 2050 and further to 11.3%–15.9% by 2070, depending on the scenario. These findings highlight the need for targeted conservation strategies to address the emerging conservation gap for brown bears in the Mediterranean, Irano‐Turanian, and Euro‐Siberian regions. Enhancing connectivity between fragmented habitats and reassessing the status of protected areas are critical actions to safeguard the brown bear population in Türkiye. This study underscores the pressing conservation challenges and strategic opportunities for securing the future of brown bears in Türkiye.